2011
DOI: 10.4137/cmwh.s5125
|View full text |Cite
|
Sign up to set email alerts
|

Atosiban in the Management of Preterm Labour

Abstract: Abstract:The purpose of this review was to look at the evidence available for the use of atosiban as a tocolytic in cases of threatened preterm labour. A Royal College of Obstetricians and Gynaecologists Green Top Guideline concluded that there was no clear evidence to show a benefit to tocolysis in reducing perinatal and neonatal morbidity and mortality. Using a systematic literature search, we summarise the evidence available on the use of atosiban for the prevention of preterm birth and compare it with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Atosiban has been shown to significantly reduce uterine contractions during PTB and delay labor by up to 48 h, without conferring significant maternal, fetal, or neonatal adverse effects [8,78,79]. One meta-analysis and multiple other studies have found no significant differences in rates of delivery at 48 h when comparing atosiban with a placebo, betamimetics, or calcium channel blockers (CCBs) [16,80,81]. Data are not available to suggest atosiban improves neonatal outcomes, but its lower discontinuation rate and safer side effect profile have led some studies to conclude that atosiban is preferable to betamimetics [16,80,81].…”
Section: Oxytocin Antagonism: Hope For Atosibanmentioning
confidence: 99%
See 2 more Smart Citations
“…Atosiban has been shown to significantly reduce uterine contractions during PTB and delay labor by up to 48 h, without conferring significant maternal, fetal, or neonatal adverse effects [8,78,79]. One meta-analysis and multiple other studies have found no significant differences in rates of delivery at 48 h when comparing atosiban with a placebo, betamimetics, or calcium channel blockers (CCBs) [16,80,81]. Data are not available to suggest atosiban improves neonatal outcomes, but its lower discontinuation rate and safer side effect profile have led some studies to conclude that atosiban is preferable to betamimetics [16,80,81].…”
Section: Oxytocin Antagonism: Hope For Atosibanmentioning
confidence: 99%
“…One meta-analysis and multiple other studies have found no significant differences in rates of delivery at 48 h when comparing atosiban with a placebo, betamimetics, or calcium channel blockers (CCBs) [16,80,81]. Data are not available to suggest atosiban improves neonatal outcomes, but its lower discontinuation rate and safer side effect profile have led some studies to conclude that atosiban is preferable to betamimetics [16,80,81]. Like other tocolytic agents, long-term maintenance therapy with atosiban has generally not been shown to delay PTB beyond 48 h, and a meta-analysis suggested maintenance therapy was associated with a significantly higher incidence of injection site reaction when compared with a placebo [9,81].…”
Section: Oxytocin Antagonism: Hope For Atosibanmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications of the native hormone structure, introduced in these peptides, are aimed at increasing their proteolytic stability and improving their pharmacokinetic characteristics. 12−14 Terlipressin differs from Lys 8 -vasopressin by increasing the peptide chain by three glycine residues at the N-terminal; thus, it is a prodrug of Lys 8 -vasopressin, converting into it with a half-life of about 6 h by gradual cleavage of glycine residues. 13,14 In atosiban and desmopressin, replacing the N-terminal cysteine residue with mercaptopropionic acid (Mpa) prevents their rapid enzymatic degradation by aminopeptidases and increases their half-life from minutes to several hours (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The presented study was conducted on atosiban (Figure ), which is a disulfide-containing cyclic octa-peptide that functions as an inhibitor of the hormones oxytocin and vasopressin and is used as a labor repressant (tocolytic) to halt premature labor. It is commercialized by Ferring Pharmaceuticals under the trade name Tractocile …”
Section: Introductionmentioning
confidence: 99%